MENEJMEN RISIKO DALAM PERFEKTIF ISLAM - Supriyo Supriyo (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2017)
Human life with all its activities in order to meet the needs of life always will always faced the possibility of risk either directly or indirectly, can occur in the short term or long term. A possibility of the occurrence or risk had certainly will affect the activity to be done And adversely affect the economy of a family and even a company, if the risks that occur have a vital impact on the family or an organization. Many failures within a company's organization are due to unforeseen risks occurring as for example the company never thinks that a newly established company is still in the short run abruptly because a workforce lacking control in the production system creates a great fire and spends all and has a bad impact For the economy of a family and even a company, if the risks that occur have a vital impact on the family or an organization. Many failures within a company's organization are due to unforeseen risks occurring as for example the company never thinks that a newly established company is still in the short run abruptly because a workforce lacking control in the production system creates a terrible fire and consumes all the company's assets Newly established. Everyone or anyone else would not want the incident to happen and befall themselves and his business in the future. Keywords: Islamic perspective, Risk management